Crianças anunciadas com queixa escolar : estudo sobre significações e implicações na representação de si - Santos, Ruzia Chaouchar dos (2018)
The current investigation, based in a psycho-social approach, proposes to identify and to analyze the children’s signification about the scholarly complain and its implication in the self representation, according to children from a municipal school, located in Cuiabá – MT. The conjecture that lays the foundation of this research includes children as social actors that are able to tell their own existence through manifold forms of language and assumes the school universe as the privileged social space to the legitimization of the recognition of its competence and of the exercise of its right to social participation (JENKS, 2005; CORSARO, 2005, 2011; SARMANETO, 2007). The theoreticalreflexive elaborations built are sustained by the approximations between the theoretical marks of the social representation theory (MOSCOVICI, 1978, 2012, 2015; JODELET, 2001, 2005, 2007; JOVCHELOVITCH, 1998, 2008; MARKOVÁ, 2006, ABRIC, 1998; ARRUDA, 2002, 2014; BAUER, 2013; DUVEEN, 1996, 2013; CASTORINA, 2013), based in an onto-genetic approach (DUVEEN; LLOYD, 2008), and in the historicalcultural theory (VIGOTSKI, 2000, 2009a, 2009b, 2010; PRESTES, 2010, 2013; MOLON, 1999, 2000). The methodological precept that oriented the plan of generation and analysis of the data were based upon the plurimetodology principles and of triangulation (APOSTOLIDIS, 2006) inspired by ethnographic outlines (ANDRÉ, 1995; ROCKWELL, 2015; EZPELETA; ROCKWELL, 1986; EZPELETA, GEERTZ, 2008). The procedure of the participant observation of the everyday dynamics was privileged combined with the realization of semi-structured interview with the participants. It was done a comprehensive analysis of the generated data through the adoption of these methodological strategies elucidated. The results show that the social knowledge shared by the children about school experience are permeated with different paradigms that tension the representational field around the children that are identified as far from the normative standard of schooling. It is notable the predominance of the adhesion to the hegemonic discourses focused in the tradition of the schooling culture, rooted in presuppositions that are adaptationists, disciplinary and uniforming which concentrate on the learner as a passive person full of impossibilities. It is also noted that, in a lower level of sharing, the emergence of a network of meanings founded in the emancipator principle that tension the transmutation of the reported view highlighting the social participation of the child in the unfolding of the various and possible ways that delineate the teaching-learning process, guided by the dialogical encounter with the Other - adult and child - authorizes the unveiling of the unpredictable.